Clinical anatomy for dummies - Terfera, David; Jegtvig, Shereen (For dummies, 2012)
The authors focus on specific structures and issues that people may encounter in a clinical setting, to present a friendly, unintimidating overview of the material covered in a typical college-level clinical anatomy course.